Streamlined multi-scenario revocation method leveraging blockchain and auxiliary trees - Satish Babu, Battula Venkata; Babu, Kare Suresh; Kare, Durga Prasad (Institute of Advanced Engineering and Science, 2024)
Access revocation is a fundamental aspect of modern information systems, ensuring that data remains secure and authorized personnel have appropriate access rights. However, existing access revocation methods address only one type of scenario, offering either partial or complete revocation functionalities but not both, leading to limitations in flexibility and effectiveness. This paper introduces a novel approach called streamlined multi-scenario revocation method (SMSRM) that combines block chain technology and auxiliary trees to streamline the process of multi-scenario access revocation. The SMSRM method defines two separate revoke request formats for partial and complete revocation. Auxiliary trees are used to keep track of non-revoked users, which is very important during the revocation process. In addition, the proposed method utilizes a block chain to record each and every revocation-related operation to provide forward secrecy. Through a comparative analysis, we evaluate the performance of our approach against existing methods. The results highlight that our method performs better in terms of response time and various performance metrics.